PENGARUH PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE TGT (TEAMS GAMES TOURNAMENT) TERHADAP HASIL BELAJAR MATA PELAJARAN IPAS SISWA KELAS V SD NEGERI NAYU SURAKARTA TAHUN PELAJARAN 2025/2026 - Fadlila Widyawati, Herlina; Rizkasari, Elinda; Mustofa, Mukhlis (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to determine the effect of the Teams Games Tournament (TGT) cooperative learning model on the learning outcomes in the Natural and Social Sciences (IPAS) subject for fifth-grade students at SD Negeri Nayu Surakarta during the 2025/2026 academic year. Employing a quantitative approach and a One-Group Pretest-Posttest design, the study involved 27 students from class VB as subjects. Data were collected using a multiple-choice test instrument consisting of 20 items that had been validated for validity, reliability, discriminating power, and difficulty level. Data analysis involved the Shapiro-Wilk normality test and hypothesis testing using a paired-sample t-test, supported by SPSS version 25 software. The findings indicate that the mean pretest score of 60.56 increased to 77.96 in the posttest. The paired-sample t-test results showed a calculated t-value of 10.266, which exceeded the t-table value of 2.056; consequently, the null hypothesis (H₀) was rejected and the alternative hypothesis (Hₐ) was accepted. Furthermore, the Cohen's Effect Size calculation yielded a value of 1.66, falling into the